2022
DOI: 10.1021/acs.macromol.2c00605
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Polymer Membranes beyond Linear Response

Abstract: The permeability of a membrane to solute penetrants is well defined on the linear response level simply as the ratio of penetrants' flux and concentration gradient at the membrane boundary layers. However, nonlinearities emerge in the flux−force relation j(f) for large driving forces f, in which the definition of permeability becomes ambiguous. Here, we study nonequilibrium membrane permeation orchestrated by a generic driving force using penetrant-and monomer-resolved computer simulations of transport in a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…Since PNIPAM exhibits a volume transition temperature similar to that of human body temperature, so it is widely used as a responsive polymer 260 . In order to develop the drug delivery applications, it becomes essential to study the molecular transport in thermoresponsive polymer membranes 261–263 . In 2018, Kanduc et al 259 elucidated the diffusion behavior of polar and nonpolar penetrants in PNIPAM hydrogels using MD based simulations.…”
Section: Characterization Of Pristine and Nanoparticle‐reinforced Hyd...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since PNIPAM exhibits a volume transition temperature similar to that of human body temperature, so it is widely used as a responsive polymer 260 . In order to develop the drug delivery applications, it becomes essential to study the molecular transport in thermoresponsive polymer membranes 261–263 . In 2018, Kanduc et al 259 elucidated the diffusion behavior of polar and nonpolar penetrants in PNIPAM hydrogels using MD based simulations.…”
Section: Characterization Of Pristine and Nanoparticle‐reinforced Hyd...mentioning
confidence: 99%
“…260 In order to develop the drug delivery applications, it becomes essential to study the molecular transport in thermoresponsive polymer membranes. [261][262][263] In 2018, Kanduc et al 259 elucidated the diffusion behavior of polar and nonpolar penetrants in PNIPAM hydrogels using MD based simulations. The PNIPAM was modeled using an OPLS-based force field.…”
Section: Stimuli-response Hydrogels Using Md-based Simulationsmentioning
confidence: 99%
“…Without this term, which is small at low cargo concentrations, the DDFT is equivalent to the Smoluchowski approach. 70 Performing the functional differentiation, the corresponding chemical potential reads as 32,33,44 bm c ðr; tÞ ¼ ln r c ðr;…”
Section: Theorymentioning
confidence: 99%
“…Without this term, which is small at low cargo concentrations, the DDFT is equivalent to the Smoluchowski approach. 70…”
Section: Theorymentioning
confidence: 99%
“…Decades ago, a spirited debate emerged over which approach is appropriate for swollen membranes (7)(8)(9)(10)(11)(12), which persists to this day. Variants of both models continue to be discussed and criticized, for example, in treating reverse osmosis membranes (13,14), with ongoing reframing of the classical models (15,16). For example, recent neutron scattering studies of water transport in polyamide reverse osmosis (PARO) membranes suggested SD to be invalid and motivated a proposed change in the strategic design of future PARO membranes, toward reducing tortuosity rather than enhancing selective solubility and diffusivity (17).…”
mentioning
confidence: 99%